(untitled) (Journal of Engineering, 2016)
The research aims to identify the level of balance in the architectural thought influenced by the rational type human consciousness, the materialistic based on the Empirical type, moral based on human experience as source of knowledge. This was reflected in architecture in the specialized thought that the mind is the source of knowledge which explains the phenomena of life. The rational approach based on objectivity and methodology in (Form Production), the other approach is based on subjectivity in form production (Form Inspiration). The research problem is that there is imbalance in the relationship between the rational side and the human experience in architecture, which led into imbalance between theory and application in architecture according to architectural movements.